Outcomes in COVID-19 Positive Neonates and Possibility of Viral Vertical Transmission: A Narrative Review - Sheth, Sudip; Shah, Nidhi; Bhandari, Vineet (American Journal of Perinatology, 2020)
Objective Novel coronavirus disease 2019 (COVID-19) seems to affect adults and pediatric patients differently. While neonates are a special population, little is known about the neonatal outcomes. This study aimed to investigate the outcomes in COVID-19 positive neonates and incidence of vertical transmission of the virus by reviewing available literature.Study Design This study is a narrative review of available literature on “COVID-19 in neonates,” for which PubMed and Google Scholar were used to search the published articles.Results We summarized the data from 39 published studies that are comprised of 326 COVID-19 positive peripartum mothers with respective neonatal outcomes. Twenty-three neonates have been reported to be COVID-19 positive. Male neonates were affected significantly more (79%) than female neonates. Approximately 3% neonates acquired infection through suspected vertical transmission. Strict infection prevention measures during the perinatal time can significantly reduce the chance of horizontal transmission of the virus. Overall, neonates were asymptomatic or mildly symptomatic regardless of gestational age at birth and required only supportive measures. There was 0% mortality in COVID-19 positive neonates.Conclusion From available published data to date, we can conclude that the prognosis of COVID-19 positive neonates is good with no mortality. There appears to be minimal vertical transmission of the infection.Key Points
Keywords: COVID-19; novel coronavirus 2019; SARS-CoV-2; neonates; neonatal outcomes; vertical transmission